Quantifying Dental Office–Originating Adverse Events: The Dental Practice Study Methods. Issue 8 (5th December 2021) - Tokede, Oluwabunmi; Walji, Muhammad; Ramoni, Rachel; Rindal, Donald B.; Worley, Donald; Hebballi, Nutan; Kumar, Krishna; van Strien, Claire; Chen, Mengxia; Navat-Pelli, Shaked; Liu, Hongchun; Etolue, Jini; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Preventable medical errors in hospital settings are the third leading cause of deaths in the United States. However, less is known about harm that occurs in patients in outpatient settings, where the majority of care is delivered. We do not know the likelihood that a patient sitting in a dentist chair will experience harm. Additionally, we do not know if patients of certain race, age, sex, or socioeconomic status disproportionately experience iatrogenic harm. Methods: We initiated the Dental Practice Study (DPS) with the aim of determining the frequency and types of adverse events (AEs) that occur in dentistry on the basis of retrospective chart audit. This article discusses the 6-month pilot phase of the DPS during which we explored the feasibility and efficiency of our multistaged review process to detect AEs. Results: At sites 1, 2, and 3, respectively, 2 reviewers abstracted 21, 11, and 23 probable AEs, respectively, from the 100 patient charts audited per site. At site 2, a third reviewer audited the same 100 charts and found only 1 additional probable AE. Of the total 56 probable AEs (from 300 charts), the expert panel confirmed 9 AE cases. This equals 3 AEs per 100 patients per year. Patients who experienced an AE tended to be male and older and to have undergone more procedures within the study year. Conclusions: This article presents an overview of the DPS. It describes the methods used and summarizes the results of its pilot phase. To minimize threats to dental patient safety, a starting point is to understand their basic epidemiology, both in terms of their frequency and the extent to which they affect different populations.